Fear of Incompetence in Intergenerational Relationships with a Family Member with Dementia. Issue 4 (2nd October 2019) - Miron, Anca M.; Thompson, Ashley E.; Bagley, Aaron; Anderson, Jessica; Melotik, Emma; Rowley, Sarah
ABSTRACT: Particularly in intergenerational relationships, family members feel they lack the knowledge and skills necessary for successful interaction with their loved ones with dementia, which leads to fear of incompetence . We examined the antecedents and outcomes of fear of incompetence, defined as the fear of being unable to interact, communicate, or take care of a close family member with dementia. Ninety-two participants completed a questionnaire about a family member with dementia. Fear of incompetence was predicted by severity of dementia symptoms and predicted increased negative stereotyping and decreased desired sensory interaction. We offered recommendations for designing effective intergenerational interaction strategies.